Impact of low‐dose tadalafil on adverse events after low‐dose‐rate brachytherapy for prostate cancer: A bi‐center randomized open‐label trial. (7th February 2021) - Minagawa, Tomonori; Oguchi, Tomohiko; Saitou, Tetsuichi; Fukazawa, Ayumu; Hashida, Iwao; Koiwai, Keiichiro; Iijima, Kazuyoshi; Kato, Haruaki; Ogawa, Teruyuki; Ishizuka, Osamu
Abstract : Objective: To study the efficacy of phosphodiesterase‐5 inhibitor tadalafil in attenuating adverse events after low‐dose‐rate brachytherapy for prostate cancer. Methods: This was a randomized open‐label trial, conducted at two institutions. Prostate cancer patients undergoing low‐dose‐rate brachytherapy were randomly assigned to receive tadalafil (study group) or tamsulosin (control group). The primary endpoint was International Prostate Symptom Score for subjective evaluation of lower urinary tract symptoms. Uroflowmetry, postvoid residual urine volume, and Sexual Health Inventory for Men score were the secondary endpoints. Each clinical variable was evaluated during a follow‐up period of 1 year after low‐dose‐rate brachytherapy. Results: A total of 107 patients were enrolled in this study, with a final total of 96 patients analyzed. The mean total International Prostate Symptom Score changes at 1, 3, 6, 9, and 12 months after low‐dose‐rate brachytherapy were +7.4, +7.1, +4.7, +1.5, and +0.8, respectively, in the tamsulosin group, and +8.5, +9.2, +6.4, +4.1, and +1.6, respectively, in the tadalafil group. There were no statistically significant differences in International Prostate Symptom Score with the exception of the score at 9‐month follow‐up. Moreover, there were no statistically significant differences in any of the uroflowmetry or postvoid residual urine volume findings. The Sexual Health Inventory for Men score in the tadalafil group was significantly higher than that in the tamsulosin group at 6, 9, and 12 months after low‐dose‐rate brachytherapy. Conclusions: Tadalafil could be an effective option for the management of lower urinary tract symptoms after low‐dose‐rate brachytherapy.